1994
DOI: 10.1002/vis.4340050406
|View full text |Cite
|
Sign up to set email alerts
|

Super TEX‐SIM: Interactive textile design and simulation

Abstract: This paper presents an interactive tool for designing and simulating textile images. It comprises a yarn editor, a textile editor and a texture mapper. These subsystems share a colour editor that can modify the colours of yarn and textile images interactively. We describe how yarn and textile images are generated, and how they are mapped to a target picture read from an image scanner. The user interface in the tool has many useful functions so that users can design textile images without knowledge of computer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The oldest paper related to smart textiles published in the Scopus database dates back to 1989. A detailed review of the ten earliest articles [84][85][86][87][88][89][90][91][92][93] showed that the research…”
Section: Analysis Of Oldest and Most Cited Documentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The oldest paper related to smart textiles published in the Scopus database dates back to 1989. A detailed review of the ten earliest articles [84][85][86][87][88][89][90][91][92][93] showed that the research…”
Section: Analysis Of Oldest and Most Cited Documentsmentioning
confidence: 99%
“…A detailed review of the ten earliest articles [84][85][86][87][88][89][90][91][92][93] showed that the research topics of these publications had little to do with smart textiles as they are defined today, yet indirectly provided the seeds for smart production of smart textiles in the future. They dealt with computer-aided design and technology in the garment industry [84,85], the use of powerful measurement technologies for fabric properties during sewing [87,90,91,93], and the simulation of textile images through the joint use of a yarn editor, a textile editor, and a texture mapper [89]. These approaches to developing and integrating new technologies led to improvements in production efficiency, flexibility, quality, and design features in the garment industry.…”
Section: Analysis Of Oldest and Most Cited Documentsmentioning
confidence: 99%
“…The applications developed cover a wide field, which includes development of algorithms to aid textile design 10, interactive applications for the design and simulation of textile images 11, applications relating to descriptive geometry 12, multimedia tools for distance learning 13, visualization of visual characteristics using fractal geometry 14, CAD interfaces 15, and 3D software graphics 16.…”
Section: Software Revisionmentioning
confidence: 99%